'It's incredible – trust me': exploring the role of celebrity athletes as marketers in online social networks. (1st January 2011) - Hambrick, Marion E.; Mahoney, Tara Q.
Sport marketers have acknowledged the popularity of online social networks, but have struggled with transforming them into viable revenue generators. Using celebrity athletes to promote products via online social networks such as Twitter may represent one potential revenue opportunity. This study examined how Lance Armstrong and Serena Williams used Twitter for promotional purposes and utilised content analysis to analyse their combined 7, 202 Twitter messages. The celebrity athletes wrote promotional messages 12% of the time, primarily to promote their corporate sponsors and products, charitable organisations and personal activities. Twitter represents a unique marketing resource and communication channel for celebrity athlete product endorsements.